ANALISIS KEMAMPUAN LITERASI DAN NUMERASI DITINJAU DARI SOAL AKM BERORIENTASI KONTEKS SAINTIFIK DAN SOSIAL BUDAYA PADA MATERI KESETIMBANGAN ASAM DAN BASA - Sri Haryani; Dian Pratiwi; Sri Wardani (EDUSAINS, 2023)
Currently, the MCA (Minimum Competency Assessment) program is part of the National Assessment to measure minimum literacy and numeracy competencies. MCA questions consist of various content, various contexts and several levels of cognitive levels. This quantitative descriptive research is focused on analyzing the literacy and numeracy abilities of students in solving MCA questions that are integrated with scientific and socio-cultural contexts. Data collection was carried out using a questionnaire and MCA test instruments. The results of this study indicate that the minimum competence of students is mostly at the proficient level of 42%. The greatest achievement of the cognitive level of reading literacy is at the level of evaluating and reflecting because the discourse and phenomena presented in the questions are often encountered by students. The lowest achievement is at the understanding level because it requires the ability to analyze and associate information with the concepts that students have. The achievement of the highest cognitive level of numeracy literacy is at the knowing level because students can carry out basic calculation operations and change variables according to the information in the items. The lowest achievement at the reasoning level was because students had never found the type of questions that required the ability to analyze, predict, and take strategies to solve the items..